Effect of Adding Mashed Potato on Physiochemical and Sensorial Properties of Masyaura - Bhattarai, Geeta; Bhandari, Sanjay; Khadka, Dambar Bahadur (Himalayan Journal of Science and Technology, 2018)
Masyaura, an ethnic, fermented and dried, cone shaped, black or green gram product, is prepared by Nepalese people living in the Himalayas. Masyaura is especially prepared from split black gram (Phaseolus mungo) and Colocasia (Colocasia esculenta) or radish and ash gourd depending upon the availability of raw materials. The taste and texture are the fundamental characteristics of Masyaura. Breakage or loss of integrity after drying, during handling, packing and cooking are observed as a common problems of Masyaura. In this study, effect of addition of mashed potato on physiochemical and sensory quality of Masyaura was studied. Masyaura prepared by using black gram and colocasia tuber in the ratio 2:1 with fermentation time of 2 h was taken as control. Black gram was partially replaced by different proportion of mashed potato (6.25, 12.5, 18.75 and 25 parts by weight) to study the effect on physiochemical and sensory quality of Masyaura. Rehydration ratio, bulk density and disintegration time of Masyaura varied from 2.60:1 to 3.45:1, 510 to 654 kg/m3 and 35.75 to 45.91 min respectively. Masyaura prepared by incorporating mashed potato had higher bulk density, longer disintegration time and lower rehydration ratio compared to control. Sensory evaluation showed that 18.75 parts mashed potato incorporated Masyaura had the best sensory quality of all the proportions studied. Incorporation of mashed potato in partial replacement of black gram could significantly improve the textural property of Masyaura.